Comparison of postoperative analgesic effect of caudal bupivacaine with and without ketamine in Pediatric subumbilical surgeries - Sharon P Aliena; Chacko Lini; John J Chirayath (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Management and assessment of postoperative pain in children is often a tough task as they cannot effectively communicate their discomfort. Caudal block is an excellent means of providing postoperative analgesia. In this study, we compared the postoperative analgesic effect of bupivacaine with and without ketamine when given caudally in children undergoing subumbilical surgeries. Material and Methods: Fifty-eight American Society of Anesthesiologists grades I and II children of either gender undergoing subumbilical surgeries were randomly allocated into two groups B and BK of 29 each. Group B received 0.75 ml/kg 0.25% bupivacaine and Group BK received 0.75 ml/kg 0.25% bupivacaine plus ketamine 0.5 mg/kg. A standardized anesthetic protocol was used. The duration of postoperative analgesia, motor block, sedation score, and hemodynamic parameters were assessed. Statistical analysis was performed using Mann-Whitney U test, independent-samples t-test, and Chi-square test. Results: The hemodynamic parameters and motor block were comparable between the groups. Duration of analgesia was prolonged in Group BK compared to Group B 11.3 ± 2.2, vs. 7.0 ± 2.3 hours, p < 0.001. However, sedation score was found to be higher in BK group compared to B Group (P < 0.001). Conclusion: Ketamine as an adjuvant to bupivacaine in caudal block is associated with a significant prolongation of postoperative analgesia.